2019
DOI: 10.1039/c9cp04554f
|View full text |Cite
|
Sign up to set email alerts
|

From benzene to naphthalene: direct measurement of reactions and intermediates of phenyl radicals and acetylene

Abstract: First-time measurement of time evolution of the main products and critical intermediates on phenyl HACA pathways with a validated pressure-dependent model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Indeed, their calculated energies are at least 43 kcal/mol more stable than 2‐C 10 H 7 + C 2 H 2 . At intermediate temperatures, resonance‐stabilized radicals with aromatic rings have been found to have longer lifetimes than other radicals 24 . Optimized geometries for species 1‐N14, 2‐N16, and 2‐N17 were previously reported by Park et al, 61 and we recalculated them at the G3(MP2,CC)//B3LYP/6‐311G ** level of theory, whereas to our knowledge 2‐N14 has not previously been reported in the literature.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Indeed, their calculated energies are at least 43 kcal/mol more stable than 2‐C 10 H 7 + C 2 H 2 . At intermediate temperatures, resonance‐stabilized radicals with aromatic rings have been found to have longer lifetimes than other radicals 24 . Optimized geometries for species 1‐N14, 2‐N16, and 2‐N17 were previously reported by Park et al, 61 and we recalculated them at the G3(MP2,CC)//B3LYP/6‐311G ** level of theory, whereas to our knowledge 2‐N14 has not previously been reported in the literature.…”
Section: Resultsmentioning
confidence: 87%
“…Parker et al 32 suggested the intramolecular H‐transfer converting 2‐C 10 H 7 to 1‐C 10 H 7 must be fast to explain the formation of ACN from 2‐C 10 H 7 + C 2 H 2 . This process was considered in this work by including the pressure‐dependent reactions on the C 10 H 7 PES, including isomerization between 1‐C 10 H 7 and 2‐C 10 H 7 , from previously reported calculations 24,55 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the crucial feature of the HACA mechanism is the kinetic‐thermodynamic coupling of H abstraction and carbon addition steps and not the particular nature of the carbon species added, 2,5 in combustion environments under soot‐forming conditions, acetylene is believed to be the most essential growth species because of the high abundance in flames owing to its thermal stability 6‐12 . The “classical” acetylene‐based HACA mechanism is generally successful in kinetic modeling of the PAH growth in various flames and has been directly confirmed by molecular beam experiments in pyrolytic reactors for the formation of naphthalene from benzene, 13‐15 phenanthrene from biphenyl, and pyrene from phenanthrene 16,17 . However, according to theoretical calculations 18 and experiments in the pyrolytic reactor, 19 classical HACA does not produce benzenoid tricyclic PAHs phenanthrene and anthracene from bicyclic naphthalene under typical combustion conditions forming instead acenaphthylene with two six‐ and one five‐member ring.…”
Section: Introductionmentioning
confidence: 99%